(untitled) (Comparative & International Education Series, 2022)
This mixed-method study explores the conditions of students with disabilities in Nepal during the pandemic. The findings reveal some unique challenges students face with disabilities (SwDs) during the pandemic. The most pressing challenge was identified as the financial challenge. Other challenges included transportation, social and attitudinal issues, and inadequate teaching and learning materials in Higher Education Institutes (HEIs) for SwDs, particularly the incompatibility of the infrastructure of HEIs, with little or no accommodation for STDs. Recommendations are offered for the improvement of an inclusive education environment. Based on the challenges experienced by the participants, some areas need immediate attention, which includes financial support, scholarship, appropriate equipment for the SwDs, special libraries and laboratories for SwDs, disable friendly toilets, awareness, and the unique campaigns for the people of their community, specially trained teachers, Co-operative friends, and families, and Technological and online supports for STDs. How to cite in APA: Manandhar, R., & Gaulee, U. (2022). Students with disabilities of higher education in Nepal during a pandemic. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 119-130). STAR Scholars.